The heavy-tailed valence hypothesis: the human capacity for vast variation in pleasure/pain and how to test it - Gómez-Emilsson, Andrés; Percy, Chris (Frontiers in Psychology, 2023)
Wellbeing policy analysis often requires a cardinal interpretation of measurement scales, such as ranking happiness on an integer scale from 0-10. This approach is often criticized with calls for ordinal-only scale interpretation instead. However, ordinality is typically insufficient to drive the cost effectiveness analyses required by policy makers, limiting the practical impact of such criticisms. Our paper presents a hypothesis that challenges common pleasure/pain scales from a different perspective and leads to explicit practical alternatives for measurement and analysis.Analysis using common measurement scales implicitly imposes a constrained view of human capacity for experience, typically that our most intense experiences can only be at most ten times more intense than our mildest experiences. This paper proposes the alternative "Heavy-Tailed Valence" (HTV) hypothesis: the notion that accessible human capacity for emotional experiences of pleasure and pain spans a minimum of two orders of magnitude.We specify five testable predictions of the HTV hypothesis, differentiating a "constrained valence" psychology from an HTV psychology. A pilot survey (n=97) then tested two of these empirical predictions, finding tentative support for the hypothesis. For instance, over half of respondents said their most intense experiences were at least twice as intense as the second most intense, implying a wide capacity overall. Simulations further demonstrate that such a result is more consistent with underlying heavy-tailed distributions of experience than a "constrained valence" psychology. Finally, we discuss lessons learned for a future survey, practical guidelines for existing analyses, and potential implications for current wellbeing policy, arguing for a dramatic increase in policy ambition. Even in high average income countries, the HTV hypothesis suggests we remain far further below our wellbeing potential than a surface reading of the data might suggest.